2000
DOI: 10.1021/jp000079u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Solvent Environment on the Spectroscopic Properties and Dynamics of the Lowest Excited States of Carotenoids

Abstract: The spectroscopic properties and dynamics of the lowest excited singlet states of peridinin, fucoxanthin, neoxanthin, uriolide acetate, spheroidene, and spheroidenone in several different solvents have been studied by steady-state absorption and fast-transient optical spectroscopic techniques. Peridinin, fucoxanthin, uriolide acetate, and spheroidenone, which contain carbonyl functional groups in conjugation with the carbon-carbon π-electron system, display broader absorption spectral features and are affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

51
634
5
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 295 publications
(696 citation statements)
references
References 38 publications
51
634
5
2
Order By: Relevance
“…A similar dependence of spectral shape on solvent polarity was reported for several naturally occurring substituted carotenoids and assigned to the formation of an intramolecular charge transfer (ICT) state (23,27). The ICT state is thought to arise from the presence of a carbonyl moiety in conjugation with the extended -electron system; the carbonyl moiety accumulates electron density upon photoexcitation.…”
Section: -3 In Acetonesupporting
confidence: 56%
See 1 more Smart Citation
“…A similar dependence of spectral shape on solvent polarity was reported for several naturally occurring substituted carotenoids and assigned to the formation of an intramolecular charge transfer (ICT) state (23,27). The ICT state is thought to arise from the presence of a carbonyl moiety in conjugation with the extended -electron system; the carbonyl moiety accumulates electron density upon photoexcitation.…”
Section: -3 In Acetonesupporting
confidence: 56%
“…The ICT state is thought to arise from the presence of a carbonyl moiety in conjugation with the extended -electron system; the carbonyl moiety accumulates electron density upon photoexcitation. The ICT and S 1 states may effectively behave as one state (27) or as distinct molecular states that equilibrate rapidly upon population from the optically allowed S 2 state (28). The carotenoids in this study also feature carbonyl groups.…”
Section: -3 In Acetonementioning
confidence: 99%
“…The spectra of Chl a and Chl b in ethanol were shifted between 4 and 7 nm to account for the small effect of environment on the Chl peak positions and to align the spectra better with the absorption maxima of the CP26 complexes. The dashed lines represent the absorption spectra of the various xanthophylls (Xanth) taken in ethanol and shifted by between 18 and 22 nm to accommodate the large spectral shift associated with the change in polarizability of the medium (40,41). No changes in the overall line shapes of the spectra of the xanthophylls were required to simulate the absorption or excitation profiles of the CP26 complexes because it has been demonstrated that for xanthophylls lacking carbonyl functional groups, no effect on the width or vibronic structure is associated with changes in solvent environment (41).…”
Section: Resultsmentioning
confidence: 99%
“…The dashed lines represent the absorption spectra of the various xanthophylls (Xanth) taken in ethanol and shifted by between 18 and 22 nm to accommodate the large spectral shift associated with the change in polarizability of the medium (40,41). No changes in the overall line shapes of the spectra of the xanthophylls were required to simulate the absorption or excitation profiles of the CP26 complexes because it has been demonstrated that for xanthophylls lacking carbonyl functional groups, no effect on the width or vibronic structure is associated with changes in solvent environment (41). For the control sample, the xanthophyll line shape was constructed from a sum of the absorption spectra of lutein, neoxanthin, and violaxanthin in a 2/1/1 molar ratio consistent with the xanthophyll composition of the reconstituted CP26 complex ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This effect has been attributed to the presence of an intramolecular charge transfer (ICT) state that acts in conjunction with the lowest excited singlet state S 1 (13). In PCP the dominant energy transfer pathway from peridinin to Chl-a is via this S 1 /ICT state, whose lifetime is Ϸ2.5 ps in the PCP complex, corresponding to an efficiency of 80% for this preferred route (14)(15)(16).…”
mentioning
confidence: 99%